Phase 1 Study of the Safety, Tolerability, and Pharmacokinetics of Vaborbactam and Meropenem Alone and in Combination following Single and Multiple Doses in Healthy Adult Subjects - Rubino, Christopher M.; Bhavnani, Sujata M.; Loutit, Jeffery S.; Morgan, Elizabeth E.; White, Dan; Dudley, Michael N.; Griffith, David C. (Antimicrobial agents and chemotherapy, 2018)
Meropenem-vaborbactam is a fixed combination of the novel β-lactamase inhibitor vaborbactam and the carbapenem antibiotic meropenem, developed for the treatment of serious infections caused by drug-resistant Gram-negative bacteria. The safety, tolerability, and pharmacokinetics (PK) of vaborbactam and meropenem following single and multiple ascending doses of each study drug administered alone or combined were evaluated in 76 healthy adult subjects in a randomized, placebo-controlled, double-blind study. Subjects were enrolled in 1 of 5 dose cohorts (receiving 250 to 2,000 mg vaborbactam and/or 1,000 to 2,000 mg meropenem) alone or in combination. No subjects discontinued the study due to adverse events (AEs), and no serious AEs were observed. The pharmacokinetics of meropenem and vaborbactam were similar when given alone or in combination; all evaluated plasma PK exposure measures (peak plasma concentration, area under the plasma concentration-time curve [AUC] from time zero to the last measurable concentration area under the plasma concentration-time curve, and AUC from time zero to infinity) were similar for the study drugs alone versus those in combination, indicating no pharmacokinetic interaction between meropenem and vaborbactam. Across all treatments, 47 to 64% of an administered meropenem dose and 75 to 95% of vaborbactam was excreted unchanged in the urine over 48 h postdose. Meropenem and vaborbactam, when given alone or in combination, have similar pharmacokinetic properties, with no plasma or urine PK drug-drug interactions, and are well tolerated. These findings supported further clinical investigation of the combination product. (This study is registered at ClinicalTrials.gov under registration no. NCT01897779.)